Combined DCT‐Haar transforms for image compression. Issue 4 (21st July 2018) - Dagher, Issam; Saliba, Mireille; Farah, Rachelle
Abstract: Discrete Cosine Transform and Haar wavelet transform are very important transforms in image compression. The objective of this paper is to combine the advantages of these 2 transforms into one transform in order to get better peak‐signal‐to‐noise‐ratio (PSNR) and keeping good compression ratio. Our first approach was to apply separately on each 8x8 block the Haar and the DCT transforms. A signaling bit along the transform which gave better PSNR are quantized and transmitted. Our second approach was to construct a new hybrid transform which is a combination of these 2 transforms. We mixed both DCT and Haar transforms into one transform. Results show that our approach outperforms the existing DCT and Haar methods giving a higher PSNR than DCT for the same compression ratio, and permitting better edge recovery than the Haar transform.